GenderUp! Because readiness is not enough when scaling for impact - Rietveld, Anne (Bioversity International and the International Center for Tropical Agriculture, 2022)
‘Achieving impact’ is what motivates many researchers working in and with the CGIAR. And so, we develop innovations that have the potential to contribute to development outcomes such as food security or climate adaptation. Once successfully tested and perhaps adopted on a small scale, such innovations need to go ‘to scale’ to achieve the desired impact(s). Scaling is not necessarily easy though. We all know about innovations which we thought would change the world, that failed to go to scale. And then there are innovations that did change the world but in ways we did not foresee nor desire, with negative consequences and impacts such as land degradation or increased (gender) inequality overshadowing the impacts that were originally strived for.